Curcumol inhibits hepatocellular carcinoma proliferation through miRNA-124/STAT3 pathway: Network pharmacology and experimental validation - Gui-yu Li; Ji-yong Lin (Current Research in Biotechnology)
Objective: Hepatocellular carcinoma (HCC) is the most common type of liver cancer and is one of the most common global cancers. Curcuma zedoaria (Christm.) Roscoe is a traditional Chinese herb that has been used for thousands of years in China to treat various types of cancer. Curcumol is one of its primary bioactive sesquiterpenes and has been reported to possess antitumor properties; however, the underlying mechanisms in hepatocellular carcinoma (HCC) are largely unknown. The aim of this study was to reveal the mechanism of curcumol treating HCC based on the network pharmacology and experimental verification. Materials and Methods: Targets of HCC and curcumol were identified. The drugs and disease targets were intersected by Venn Diagram. The KEGG pathway enrichment analysis of curcumol treating HCC was analyzed through the R 3.6.1 software. The effects of curcumol on the inhibition of HCC cell line HepG2 growth and its pro-apoptotic activity were evaluated by cell counting kit-8 and flow cytometry. The expression of microRNA-124 (miRNA-124) mRNA was detected by quantitative real-time PCR. HepG2 cells were transfected with a miRNA mimic and inhibitor. The expression of STAT3 and its phosphorylation were induced by IL-6 and detected by western blotting. Results: MicroRNAs in cancer is a significant enrichment signaling pathway for curcumol treating HCC, according to the KEGG pathway analysis. Curcumol effectively inhibited HepG2 cell growth at 50–150 μg/ml, while it had low toxicity to normal LO2 cells. Using flow cytometry, curcumol strongly promoted apoptosis in HepG2 cells and was more potent than the miRNA-124 mimic, whereas the miRNA-124 inhibitor reduced the pro-apoptotic effect of curcumol. Western blotting revealed that curcumol significantly downregulated the overexpression of STAT3 and its phosphorylation in interleukin-6 induced HepG2 cells, whereas an increased level of STAT3 was observed in the miRNA-124 inhibitor transfected cells after curcumol treatment compared to untransfected cells. The level of miRNA-124 was changed up to 5.87-fold by curcumol treatment. Conclusions: The mechanism underlying the effect of curcumol on inhibition and pro-apoptosis of HepG2 cell growth is possibly related to the miRNA-124/STAT3 pathway.